2013
DOI: 10.1371/journal.pone.0074485
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Simple Intransitive Actions: The Effect of Familiarity

Abstract: IntroductionHumans are more familiar with index – thumb than with any other finger to thumb grasping. The effect of familiarity has been previously tested with complex, specialized and/or transitive movements, but not with simple intransitive ones. The aim of this study is to evaluate brain activity patterns during the observation of simple and intransitive finger movements with differing degrees of familiarity.MethodologyA functional Magnetic Resonance Imaging (fMRI) study was performed using a paradigm consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Therefore, this higher activity might also be related with the presence of a higher degree of familiarity for experts than for novices. As some studies have described, there is more activity in the MNS when familiar actions are observed (Calvo‐Merino et al ., , ; Cross et al ., ; Muysoms et al ., ; Plata Bello et al ., ). Thus, the activity described by Abreu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, this higher activity might also be related with the presence of a higher degree of familiarity for experts than for novices. As some studies have described, there is more activity in the MNS when familiar actions are observed (Calvo‐Merino et al ., , ; Cross et al ., ; Muysoms et al ., ; Plata Bello et al ., ). Thus, the activity described by Abreu et al .…”
Section: Discussionmentioning
confidence: 97%
“…An observer's prior experience with the action being observed modifies the simulation of others’ actions . For example, the IPL is more activated by the observation of dance movements with which the observer has greater personal experience or general familiarity . More specific types of experience with action also modulate subsequent parietal activity during action observation.…”
Section: Action Implementation and Frontoparietal Circuitrymentioning
confidence: 99%
“…Intransitive actions lead to an activation of the human MNS (there is new evidence of this activation in primates too) in a more restrictive way than transitive actions do [31,32]. In fact, the activity of the MNS when intransitive actions are observed tends to predominantly activate posterior parietal regions more than premotor areas [31,33]. Minor activation of the MNS does not have to mean that an AOT based on these actions had less beneit than using transitive ones.…”
Section: Which Actions Should Be Used In Aot?mentioning
confidence: 97%